A new species of the genus Parawenhoekia (Acari: Chyzeriidae) from Montenegro - Saboori, Alireza; Pesic, Vladimir; Hakimitabar, Masoud (Zootaxa, 2008)
Parawenhoekia seadi n. sp. (Acari: Chyzeriidae) is described and illustrated from larvae ectoparasitic on adults of unidentified grasshoppers (Orthoptera: Acrididae) and male of Dolycoris barbarum (L.) (Heteroptera: Pentatomidae) from Montenegro. A key to the species of Parawenhoekia of the world (larva) is presented.